Liquidity Shocks and Corporate Resilience: Exploring the Interplay of Trade Credit and Bank Financing in Firm Performance - Eka Wahyu Kasih; A.Sigit Pramono Hadi; Cahyatih Kumandang (LPPM STIE Kasih Bangsa, 2024)
This qualitative literature review investigates the interplay between liquidity shocks and corporate resilience, focusing on the roles of trade credit and bank financing in firm performance. The review synthesizes existing research to elucidate how firms navigate liquidity constraints during economic turbulence, emphasizing the critical importance of strategic financial management. The findings reveal that liquidity shocks often compel firms to adopt conservative financial practices, which can limit their growth potential. However, effective utilization of trade credit serves as a vital buffer, allowing firms to maintain operational flexibility and mitigate risks associated with funding constraints. Furthermore, the review underscores the necessity for firms to employ diversified financing strategies that integrate trade credit and bank loans to enhance resilience and long-term performance. The study also highlights the evolving landscape of financial technology, which presents new opportunities for improving access to credit and supporting corporate sustainability. This review provides a foundation for future research into the complex dynamics of liquidity, trade credit, and bank financing, offering valuable insights for practitioners and policymakers alike.